Video laboratories for the teaching and learning of professional ethics in exercise physiology curricula - Senchina, David S. (Advances in physiology education, 2011)
Student researchers in physiology courses often interact with human subjects in classroom research but may be unfamiliar with the professional ethics of experimenter-subject interactions. This communication describes experiences related to an interactive video used in exercise science and general biology courses to help students become aware of, sensitive to, and comfortable with implementing professional ethics into their own thinking and behavior as researchers before entering the laboratory. The activity consisted of a filmed exercise physiology experiment complemented with interactive question sheets followed by small- and large-group discussion and culminating with individual student reflections. Student written responses from multiple courses indicated that students were able to 1) identify and consider the ethics of experimenter-subject interactions from the movie, 2) generalize broader ideas of professional ethics from those observations, and 3) consider their observations in terms of future experiments they would be conducting personally and how they should interact with human subjects. A majority of students indicated a positive reaction to the video and identified specific aspects they appreciated. It is hoped that this report will encourage other instructors to consider the use of interactive videos in the teaching and learning of professional ethics related to their courses.